3D Guided Dental Implant Placement: Impact on Surgical Accuracy and Collateral Damage to the Inferior Alveolar Nerve - Amit Mistry; Cemal Ucer; John D. Thompson; Rabia Sannam Khan; Emina Karahmet; Farooq Sher (MDPI AG, 2021)
An increase in the number of implants placed has led to a corresponding increase in the number of complications reported. The complications can vary from restorative complications due to poor placement to damage to collateral structures such as nerves and adjacent teeth. A large majority of these complications can be avoided if the implant has been placed accurately in the optimal position. Therefore, the aim of this in vitro pilot study was to investigate the effect of freehand (FH) and fully guided (FG) surgery on the accuracy of implants placed in close proximity to vital structures such as the inferior alveolar nerve (IAN). Cone-beam computed tomography (CBCT) and intraoral scans of six patients who have had previous dental implants in the posterior mandible were used in this study. The ideal implant position was planned. FG surgical guides were manufactured for each case. In this study, the three-dimensional 3D printed resin models of each of the cases were produced and the implants placed using FG and FH methods on the respective models. The outcome variables of the study, angular deviations were calculated and the distance to the IAN was measured. The mean deviations for the planned position observed were 1.10 mm coronally, 1.88 mm apically with up to 6.3 degrees' angular deviation for FH surgery. For FG surgical technique the mean deviation was found to be at 0.35 mm coronally, 0.43 mm apically with 0.78 degrees angularly respectively. The maximum deviation from the planned position for the apex of the implant to the IAN was 2.55 mm using FH and 0.63 mm FG. This bench study, within its limitations, demonstrated surgically acceptable accuracy for both FH and FG techniques that would allow safe placement of implants to vital structures such as the IAN when a safety zone of 3 mm is allowed. Nevertheless, a better margin of error was observed for FG surgery with respect to the angular deviation and controlling the distance of the implant to the IAN using R2 Gate® system.